Welcoming Wolves? Governing the Return of Large Carnivores in Traditional Pastoral Landscapes - Pettersson, Hanna L.; Quinn, Claire H.; Holmes, George; Sait, Steven M.; López-Bao, José Vicente (Frontiers in Conservation Science, 2021)
Wolf populations are recovering across Europe and readily recolonize most areas where humans allow their presence. Reintegrating wolves in human-dominated landscapes is a major challenge, particularly in places where memories and experience of coexistence have been lost. Despite the observed expansion trends, little has been done to prepare communities for the return of these apex predators, or to understand what fosters and perpetuates coexistence. In this study, we present a theoretical framework for resilient coexistence based on four conditions: Effective institutions, large carnivore persistence, social legitimacy, and low levels of risk and vulnerability, nested within the social-ecological systems concept. To empirically show how the conditions can be manifested and interconnected, and how this knowledge could be used to improve local coexistence capacities, the framework is applied in a case study of human-wolf relations in Spain. We examined three traditionally pastoral landscapes at different states of cohabitation with wolves: uninterrupted presence, recent recolonization and imminent return. We found that both the perceptions of wolves and the capacity to coexist with them diverged across these states, and that this was largely determined by a diversity of vulnerabilities that have not been recognized or addressed within current management regimes, such as economic precarity and weak legitimacy for governing institutions. Our results illustrate the importance of working in close contact with communities to understand local needs and enhance adaptive capacities in the face of rural transitions, beyond those directly related to wolves. The framework complements emerging tools for coexistence developed by researchers and practitioners, which offer guidance on the process of situational analysis, planning and resource allocation needed to balance large carnivore conservation with local livelihoods.